MEMBANGUN ORGANISASI YANG EFEKTIF MELALUI PERENCANAAN STRATEGIS YANG MEMADAI: KAJIAN PADA UPTD SKB - Sadid, Agus (JIV-Jurnal Ilmiah Visi, 2008)
The effectiveness of an organization to empower all its human resources much depends on the capability of the manager to manage the resources to complete both the goals and the objectives of the organization. This article describes how to develop an effective organization of learning center, such as SKB. It also discusses the relationship between strategic planning and an effective SKB. This article concludes (1) developing an effective SKB depends on the commitment and consistency, leaderships and the unity of perception, as well as the mission and vision of all managers in SKB; and (2) to obtain the objectives, all capacity of resources should be benefited optimally. Some advantages of having strategic planning for SKB are identified as (1) helping to focus on program, (2) giving guidelines to reach the goal, (3) developing rational frameworks, and (4) evaluating and identifying all possible obstacles.